Positive associations with native shrubs are intense and important for an exotic invader but not the native annual community across an aridity gradient. Issue 9 (29th June 2020) - Lucero, Jacob E.; Seifan, Merav; Callaway, Ragan M.; Lortie, Christopher J.
Abstract: Aim and Location: Positive interactions influence the assembly of plant communities globally, particularly in stressful environments such as deserts. However, few studies have measured the intensity and relative importance of positive interactions involving native and invasive species along aridity gradients. These measures are essential for predicting how dryland communities will respond to biological invasions and environmental change. Here, we measured the intensity and importance of positive associations formed between native shrubs and the annual plant community, which included highly invasive Bromus madritensis ssp. rubens (" B. rubens ") and native neighbours, along an aridity gradient across the Mojave and San Joaquin Deserts. Methods: Along the gradient, we sampled metrics of abundance and performance for invasive B. rubens, native annual species (pooled), exotic annual species (pooled) and all annual species (pooled) during peak flowering at 120 pairs of shrub and open microsites. Results: Across the gradient, B. rubens occurred at far greater abundance, cover, biomass and fitness near shrubs than away from shrubs. When Larrea tridentata was the focal shrub, positive effects on B. rubens abundance and cover were least intense at the most arid sites under the shortest shrubs. The native annual community occurred at greater abundance, cover and species richness away from shrubs, regardless of relative aridity or shrub traits. Community‐level species richness was greatest away from shrubs, but exotic species richness was similar in shrub and open microsites. Main conclusions: Across two deserts, B. rubens formed intense and important positive associations with native shrubs that consistently improved its abundance, cover, biomass and fitness, and for abundance and cover, the intensity of B. rubens – L. tridentata associations depended upon relative aridity and shrub height. By strongly facilitating a dominant invader but not native‐ or community‐level biodiversity, native shrubs provided the wrong kind of help to the annual plant community.